Dopamine Delivery via pH‐Sensitive Nanoparticles for Tumor Blood Vessel Normalization and an Improved Effect of Cancer Chemotherapeutic Drugs. Issue 18 (5th August 2019) - Taleb, Mohammad; Ding, Yanping; Wang, Bin; Yang, Na; Han, Xuexiang; Du, Chong; Qi, Yingqiu; Zhang, Yinlong; Sabet, Zeinab Farhadi; Alanagh, Hamideh Rezvani; Mujeeb, Ayeesha; Khajeh, Khosro; et al.
Abstract : Tumor blood vessels have been reported to be abnormal in both structure and function compared with those in normal tissues, leading to a hostile microenvironment and inadequate antitumor drug delivery. Dopamine, a chemical messenger, is proven to inhibit angiogenesis and improve tumor vessel normalization. Here, a mesoporous silicon nanoparticle (MSN) is constructed that is responsive to the weakly acidic pH of the tumor extracellular matrix for steady delivery and tumor‐localized release of dopamine. Then MSNs are functionalized with amine conjugated phenylboronicacid molecules, and dopamine is loaded by reacting with phenylboronic acid. In a weakly acidic environment, MSNs intelligently release dopamine due to the hydrolysis of boronic‐ester bond between dopamine and phenylboronic acid, resulting in an evident inhibition of vascular endothelial cell migration and tubule formation. It is shown that loading of dopamine into the functional MSNs significantly prolong the circulatory half‐life of this small molecule. After intravenous injection to tumor bearing mice, this nanoformulation induce tumor blood vessel normalization, thereby improving the antitumor chemotherapeutic efficacy of doxorubicin. This study demonstrates that the pH‐responsive MSN offers great potential for delivery of dopamine in vivo and the normalization of tumor vessels by dopamine can provide an auxiliary treatment for cancer chemotherapeutic drugs. Abstract : Normalization of tumor blood vessels can facilitate the drug delivery. Mesoporous silicon nanoparticles are modified and functionalized to deliver dopamine (DA) as a normalized factor with pH‐sensitive bond to protect it from oxidation. DA can normalize vessels formation by its effect on vascular endothelial growth factor. Normalization of vessels improves the antitumor chemotherapeutic efficiency of doxorubicin.